Do conhecimento tácito ao conhecimento explícito: A elaboração de manual de política de indexação em bibliotecas universitárias - Rubi, Milena Polsinelli [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP]; Boccato, Vera Regina Casari [UNESP] (My University, 2012)
The indexing policy establishes the guiding principles and criteria for the indexer when determining the subjects of the documents. This article shows how to capture the indexers' tacit knowledge into explicit knowledge using the group verbal protocol methodology to produce an indexing manual. Continuing professional education results to be a key factor in obtaining good results when formalizing the indexing policy of a library and keeping it up to date.
From tacit to explicit knowledge: Elaborating an indexing policy handbook for university libraries
Keywords: Continuing education; Indexing manual; Indexing policy; Organizational knowledge